Experiences of intimate partner violence and antepartum depression among women seeking antenatal care in Addis Ababa, Ethiopia: findings from the MISPOD study - Nigus Bililign Yimer; Lenka Beňová; Samson Gebremedhin; Alemnesh H Mirkuzie; Meseret Zelalem; Gracia Fellmeth; Anteneh Asefa (Scientific Reports)
Abstract Despite the high prevalence of intimate partner violence (IPV) and antepartum depression, there is limited evidence on the association between the two in Ethiopia. We aimed to investigate the association between experience of IPV during and before pregnancy and depression in the third trimester of pregnancy. We surveyed women attending antenatal care clinics in 22 selected health facilities in Addis Ababa in the third trimester of pregnancy. We used a 12-item tool to measure IPV and the Edinburgh Postnatal Depression Scale (EDPS) to measure antepartum depression. We performed multivariable logistic regression analysis to determine the association between IPV and antepartum depression. Of the 399 women included, 14.5% (95% CI: 11.3-18.5%) had symptoms suggestive of antepartum depression (EDPS score ≥ 11) and 31.6% (95% CI: 27.1-36.4%) had recently experienced some form of IPV. The adjusted odds of antepartum depression was 2.24 higher among women who had experienced IPV compared to those who had not (95% CI: 1.11–4.54). Antepartum depression was higher among women aged 15–24 compared to those aged 25–34 (AOR = 2.76, 95% CI: 1.05, 7.23), women with low maternal social support compared to those with adequate support (AOR = 7.04, 95% CI: 2.07, 23.97), and women who worried very often about feeding their family compared to those who did not worry at all (AOR = 8.95, 95% CI: 3.09, 25.94). The findings highlight the need for integrated and tailored interventions to mitigate IPV and antepartum depression to address the needs of adolescent and young women, and those living in poverty or lacking social support.